Powder Self-Emulsifying Drug Delivery System for Mitotane: In Vitro and In Vivo Evaluation - Mohamed Skiba; Valentin Lefébure; Frederic Bounoure; Nicolas Milon; Michael Thomas; Herve Lefebvre; Lahiani-Skiba Malika (MDPI AG, 2024)
Drug Delivery Systems (DDSs) of known drugs are prominent candidates for new and more effective treatments of various diseases, as they may increase drug solubility, dissolution velocity, and bioavailability. Mitotane (o,p'-dichlorodimethyl dichloroethane [o,p'-DDD]) is used for the treatment of adrenocortical cancer and, occasionally, Cushing's syndrome. However, the efficacy of mitotane is limited by its low oral bioavailability, caused by its extremely poor aqueous solubility. This research explores the development of a new powder self-emulsifying drug delivery system (P-SEDDS) for mitotane to improve its oral bioavailability. The study focuses on the new concept of a mitotane-loaded P-SEDDS to overcome the challenges associated with its limited solubility and high logP, thereby improving its therapeutic efficacy, reducing off-target toxicity, and avoiding first-pass metabolism. The P-SEDDS formulations were meticulously designed using only α-cyclodextrin and oil, with the goal of achieving a stable and efficient P-SEDDS. The optimized formulation was characterized for pharmaceutical properties, and its pharmacokinetic behavior was examined in rats. The results demonstrated a significant enhancement in the bioavailability of mitotane when delivered through the P-SEDDS, attributed to the increased dissolution velocity and improved absorption of the poorly water-soluble drug. The results suggest that a mitotane-loaded P-SEDDS has distinctly enhanced in vitro and in vivo performance compared with conventional mitotane formulations (Lysodren®), which leads to the conclusion that the P-SEDDS formulation could be a viable and effective strategy for improving the dissolution rate and bioavailability of poorly aqueous-soluble ingredients.